2002
DOI: 10.1152/ajprenal.0186.2001
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous renal blood flow autoregulation curves in conscious sinoaortic baroreceptor-denervated rats

Abstract: Pires, Silene L. S., Claude Julien, Bruno Chapuis, Jean Sassard, and Christian Barrè s. Spontaneous renal blood flow autoregulation curves in conscious sinoaortic baroreceptor-denervated rats. Am J Physiol Renal Physiol 282: F51-F58, 2002. First published August 8, 2001 10.1152/ajprenal.00186.2001.-These experiments examined whether the conscious sinoaortic baroreceptor-denervated (SAD) rat, owing to its high spontaneous arterial pressure (AP) variability, might represent a model for renal blood flow (RBF) au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
19
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 28 publications
7
19
0
Order By: Relevance
“…A striking time-associated variability of RBF was observed at any given BP in individual rats in the present study, which has also been observed previously (58,70,81). Nevertheless, despite this variability in RBF, the BP-RBF bin analysis in the present study (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…A striking time-associated variability of RBF was observed at any given BP in individual rats in the present study, which has also been observed previously (58,70,81). Nevertheless, despite this variability in RBF, the BP-RBF bin analysis in the present study (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…7, which depicts the variations in RBF and BP seen over a 2-h period in a conscious, unrestrained rat. Similar observations are reported by other laboratories (120,123,142,143). Such temporal variability may reflect the influence of neurohormonal and metabolic inputs (Fig.…”
Section: Consequences Of Impaired Renal Autoregulation On Volume Homesupporting
confidence: 89%
“…This occurs via dilation or constriction in response to alterations in blood pressure, which incite changes in circumferential wall tension. The active myogenic response closely follows an initial passive distension, as has been observed in a multitude of experimental studies (5,11,19,26,27,30,32,39,45,58,61,63).…”
Section: Vessel Modelsupporting
confidence: 69%
“…9B), with a non-zero gradient of flow with respect to pressure in the autoregulatory range due to the omission of TGF from the model. This corresponds well to data from the experimental scenario that most closely simulates the condition of purely myogenic renal autoregulation (45). To prevent bias, this data set was not used to determine the parameters used in the mathematical system.…”
Section: Whole-organ Autoregulationmentioning
confidence: 57%
See 1 more Smart Citation